2011
DOI: 10.1186/1756-0500-4-460
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal status of rheumatoid arthritis patients in khartoum state

Abstract: BackgroundFew studies have investigated the periodontal condition among Rheumatoid arthritis in Sudan. The present study described the periodontal condition among Sudanese patients suffering from rheumatoid arthritis and to compare them with those of non-rheumatic subjects.MethodsA group of eighty rheumatoid arthritis patients was selected from Patient's Rheumatoid Clinics in Khartoum State during the period of January to May 2010. A control group of eighty patients with the same age and gender was selected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
11
2
1
Order By: Relevance
“…It has long been observed that patients with PD are at a higher risk of developing RA [ 3 , 33 ], and patients with RA have increased likelihood of suffering from PD [ 34 , 35 ]. However, the mechanistic basis of this association remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been observed that patients with PD are at a higher risk of developing RA [ 3 , 33 ], and patients with RA have increased likelihood of suffering from PD [ 34 , 35 ]. However, the mechanistic basis of this association remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A high prevalence of periodontal disease was reported in patients with rheumatoid arthritis and some RA patients even experience severe periodontal disease ( 5 - 7 ). Patients with RA also have higher CAL index, more tooth loss and periodontitis ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study carried out by Abdelsalam et al in 2010 in Sudan [10] indicated a significant relationship between periodontal disease and RA and highlighted the potential for an association between these chronic inflammatory conditions among the Sudanese population.…”
Section: Introductionmentioning
confidence: 99%